2016
DOI: 10.3892/mmr.2016.6060
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of low shear stress-induced eNOS multi-site phosphorylation and nitric oxide production via protein kinase and ERK1/2 signaling

Abstract: Abstract.Physiological shear stress has been demonstrated to serve an atheroprotective function by stimulating endothelial nitric oxide synthase (eNOS) multi-site phosphorylation. Low shear stress (LSS) serves an atheroprone role by increasing endothelial cell apoptosis and inflammation. The present study assessed whether LSS inhibited nitric oxide (NO) production in human umbilical vein endothelial cells by modulating eNOS phosphorylation and potential signaling pathways. A parallel flow chamber imposed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Therefore, it is important to understand the relationship between LSS and ROS generation. Our laboratory previously showed that LSS induces ROS in a time‐dependent manner, which may involve ERK/eNOS Thr495 (Kong et al, ; Wang et al, ). De Keulenaer et al () demonstrated that laminar shear stress (5 dyn/cm 2 ) resulted in a significant time‐dependent increase in the superoxide (O 2 −) level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it is important to understand the relationship between LSS and ROS generation. Our laboratory previously showed that LSS induces ROS in a time‐dependent manner, which may involve ERK/eNOS Thr495 (Kong et al, ; Wang et al, ). De Keulenaer et al () demonstrated that laminar shear stress (5 dyn/cm 2 ) resulted in a significant time‐dependent increase in the superoxide (O 2 −) level.…”
Section: Discussionmentioning
confidence: 98%
“…The cells were cultured in RPMI‐1640 medium supplemented with 10% fetal bovine serum (GIBICO). Upon reaching 90% confluence, the cells were digested with 0.25% trypsin (GIBICO) and transferred to slides for subsequent experiments (shear stress) as described in our previous study (Kong et al, ). When the cells on slides reach 90% confluence, we exposed cells to shear stress application.…”
Section: Methodsmentioning
confidence: 99%
“…As one of the substrates for Akt1, phosphorylated eNOS generates nitric oxide in EC that regulates endothelial function, including angiogenesis and vessel dilation; 53,54 eNOS can also be regulated via ERK1/2 and p38, consistent with a complex network of signaling cascades. 55,56 Knockdown of eNOS in a murine AVF model prevents the normalization of shear stress after AVF creation and impairs outward remodeling. 57 In addition, increasing eNOS activity by knockdown of caveolin-1 promotes AVF maturation, 21 consistent with our data that activation of EphrinB2 by EphB4-Fc leading to subsequent activation of Akt1, p38, and ERK1/2 increases wall thickening during venous remodeling (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological shear stress has been demonstrated to serve an atheroprotective function by stimulating eNOS multisite phosphorylation. In our previous study, we found that LSS‑induced activation of ERK1/2/eNOS‑Thr495 served a major role in inhibiting endothelial NO synthase, which may explain the proinflammatory and proatherosclerotic properties of LSS . We further discovered that LSS strongly activated hyaluronidase 2 to degrade HA in the glycocalyx.…”
Section: Discussionmentioning
confidence: 86%
“…In our previous study, we found that LSS-induced activation of ERK1/2/eNOS-Thr495 served a major role in inhibiting endothelial NO synthase, which may explain the proinflammatory and proatherosclerotic properties of LSS. 21 We further discovered that LSS strongly activated hyaluronidase 2 to degrade HA in the glycocalyx. The dephosphorylation of eNOS-Ser-633 under LSS was triggered after HA degradation by hyaluronidase, and prevented by repairing the glycocalyx with high molecular weight hyaluronan.…”
Section: Discussionmentioning
confidence: 86%